Breaking Financial Barriers: Empowering Persons With Disabilities Through Inclusive Investment Education - Diah Febriyanti; Adnan Bahalwan; Zulhamka Julianto Kadir; Devyanthi Syarif; Iis Hanifah (Inaba of Community Services Journal, 2026)
This community service program aimed to improve financial literacy and economic empowerment among persons with disabilities through collaboration between Universitas Indonesia Membangun (INABA), the West Java Indonesia Stock Exchange (IDX), and the Bandung Independent Living Center (BILIC). The program provided education on personal financial management, capital market literacy, and safe investment practices through seminars, mentoring, and practical activities. The results showed increased understanding of financial management, greater awareness of legal investment opportunities, and enhanced motivation toward economic independence. The program highlights the importance of multi-stakeholder collaboration in promoting financial inclusion and social empowerment for persons with disabilities.